Kank regulates RhoA-dependent formation of actin stress fibers and cell migration via 14-3-3 in PI3K–Akt signaling - Kakinuma, Naoto (The Rockefeller University Press, 2008)
Phosphoinositide-3 kinase (PI3K)/Akt signaling is activated by growth factors such as insulin and epidermal growth factor (EGF) and regulates several functions such as cell cycling, apoptosis, cell growth, and cell migration. Here, we find that Kank is an Akt substrate located downstream of PI3K and a 14-3-3–binding protein. The interaction between Kank and 14-3-3 is regulated by insulin and EGF and is mediated through phosphorylation of Kank by Akt. In NIH3T3 cells expressing Kank, the amount of actin stress fibers is reduced, and the coexpression of 14-3-3 disrupted this effect. Kank also inhibits insulin-induced cell migration via 14-3-3 binding. Furthermore, Kank inhibits insulin and active Akt-dependent activation of RhoA through binding to 14-3-3. Based on these findings, we hypothesize that Kank negatively regulates the formation of actin stress fibers and cell migration through the inhibition of RhoA activity, which is controlled by binding of Kank to 14-3-3 in PI3K–Akt signaling.